2019
DOI: 10.1051/0004-6361/201936659
|View full text |Cite
|
Sign up to set email alerts
|

Vertical position of the Sun with γ-rays

Abstract: We illustrate a method for estimating the vertical position of the Sun above the Galactic plane by γ-ray observations. Photons of γ-ray wavelengths are particularly well suited for geometrical and kinematic studies of the Milky Way because they are not subject to extinction by interstellar gas or dust. Here, we use the radioactive decay line of 26 Al at 1.809 MeV to perform maximum likelihood fits to data from the spectrometer SPI on board the INTEGRAL satellite as a proof-of-concept study. Our simple analytic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Numerous studies have estimated z e using a wide variety of celestial sources, and most of these studies obtained z e in the range of 10-25 pc to the north of the Galactic plane (e.g., Joshi 2007;Majaess et al 2009;Buckner & Froebrich 2014;Yao et al 2017;Siegert 2019;Griv et al 2021). Though a direct comparison of z e in different studies is difficult, it is found that the choice of the data sample and method of determination account for most of the disagreements among z e values (Joshi 2007;.…”
Section: Solar Offsetmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have estimated z e using a wide variety of celestial sources, and most of these studies obtained z e in the range of 10-25 pc to the north of the Galactic plane (e.g., Joshi 2007;Majaess et al 2009;Buckner & Froebrich 2014;Yao et al 2017;Siegert 2019;Griv et al 2021). Though a direct comparison of z e in different studies is difficult, it is found that the choice of the data sample and method of determination account for most of the disagreements among z e values (Joshi 2007;.…”
Section: Solar Offsetmentioning
confidence: 99%
“…Moreover, the wide range of ages of OCs, from a few million years to nearly 10 billion years, provides a unique opportunity to study the evolution of the Galactic disk and trace the star formation history across the Milky Way. In recent years, the number of OCs has grown manyfold (Cantat-Gaudin 2022;Castro-Ginard et al 2022;Chi et al 2023), paving the way for a better understanding of the Galactic disk, thanks to large-scale surveys and machinelearning methods (Cantat-Gaudin et al 2018, 2019Ryu & Lee 2018;Sim et al 2019;Liu & Pang 2019;Dias et al 2021;He et al 2021;Hao et al 2022b;Castro-Ginard et al 2022). Accurate physical parameters for OCs are obtained through analysis of precise membership identification of cluster stars facilitated through their astrometric and kinematic study (Dias et al 2014(Dias et al , 2021Cantat-Gaudin et al 2018;Castro-Ginard et al 2022;Zhong et al 2022).…”
Section: Introductionmentioning
confidence: 99%